Pengembangan Multimedia Pembelajaran Interaktif IPA Materi Atmosfer Bumi Kelas VIII SMPN 3 Tulungagung - Mochammad Farid Yusuf; Anselmus JE Toenlioe; Agus Wedi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
This development research aims to produce appropriate interactive multimedia learning through validation tests on the material of the earth's atmosphere and assessing the effectiveness of the use of multimedia learning. This development uses the research and development procedure of William W. Lee and Diana L. Owens (2004) with the following steps: 1) needs analysis, 2) preliminary analysis, 3) design, 4) development, 5) implementation, 6) evaluators. The results of this development research are interactive multimedia packaged in the form of a compact disk and equipped with a manual for the use of class VIII junior high school students in science learning materials on Earth's atmosphere. Based on the results of the test material experts, media experts, and individual tests, small group tests and field tests of this learning media meet the valid criteria and are suitable for use.